Therapeutic Efficacy of Carvacrol-Loaded Nanoemulsion in a Mouse Model of Schistosomiasis - Xavier, Edilaine S.; de Souza, Rafael L.; Rodrigues, Vinícius C.; Melo, Camila O.; Roquini, Daniel B.; Lemes, Bruna L.; Wilairatana, Polrat; Oliveira, Elquio E.; de Moraes, Josué (Frontiers in Pharmacology, 2022)
Since praziquantel is the only drug available to treat schistosomiasis, a neglected parasitic disease that affects more than 240 million people worldwide, there is an urgent demand for new antischistosomal agents. Natural compound-loaded nanoparticles have recently emerged as a promising alternative for the treatment of schistosomiasis. Carvacrol is an antimicrobial monoterpene present in the essential oil extracted from several plants, especially oregano (Origanum vulgare). In this study, a carvacrol nanoemulsion (CVNE) was prepared, characterized, and administered orally (200 mg/kg) in a mouse infected with either immature (prepatent infection) or adult (patent infection) Schistosoma mansoni. For comparison, data obtained with an unloaded nanoemulsion (blank formulation), free carvacrol, and the drug of reference praziquantel are also presented. CVNE was more effective than free carvacrol in reducing the worm burden and egg production in both patent and prepatent infections. Favorably, CVNE had a high effect in terms of reducing the number of worms and eggs (85–90%) compared with praziquantel (~30%) in prepatent infection. In tandem, carvacrol-loaded nanoemulsion markedly improved antischistosomal activity, showing efficiency in reducing worm and egg burden, and thus it may be a promising delivery system for the treatment of schistosomiasis.